Qualitative Study on Endothelial Cell–to–cell–junction Disassembly in Severe Burn Injury - Moenadjat, Yefta; Siregar, Nurjati C.; Wanandi, Septelia I.; Sadikin, Mohamad (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Endothelial gap in severe burn injury remain a mystery. Capillary leaks possess its own characteristics, which is found in burned– and non–burned area. The gaps remain up to 10 post burned days or more. This is somehow representing the feature of systemic capillary leaks syndrome at the first date. VE–cadherin of adherens endothelial junction molecules known to be temporarily disassembled following thermal exposure, but there’s a question about reversibility. Question is also addressed to occludin of the tight junction molecules. We run a study to investigate these junction molecules. Method. We run an investigation to find out both molecules qualitatively descriptive on 30 burn patients enrolled, consist of 20 severe– and 10 of non–severe burn. Samples of moderate size vein taken from burned– and non–burned area were subjected to study of histomorphology and immunohistochemistry. Light microscopic study and polymerase chain reaction test were carried out to compare the features and its expression. Analysis is carried out to find the difference, specificity and sensitivity. Results. Samples took within the first 8 hours following ER presentation showed severely deteriorated endothelial lining and both ofVE–cadherin and occludin dissociation. This endothelial junction disassembly was found in both of burned– and non–burned area; both of severe– and non– severe burn as well. In burned area, mRNA expression of VE–cadherin found to be increased, as occludin decreased. In severe burned group, mRNA expression of VE–cadherin as well as occludin found to be increased. VE–cadherin synthesis was found to be earlier than occludin. Conclusion. Dissociation of both of endothelial cell–to–cell molecules junction show no differences between the two groups, and between burned– and non–burned areas.